2015
DOI: 10.1007/s12033-015-9868-z
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of Bioactive Protein A from Staphylococcus aureus (SpA) on the Surface of Bacillus subtilis Spores

Abstract: Protein A from Staphylococcus aureus (SpA) is a 40-60 kDa cell-wall component, composed of five homologous immunoglobulin (Ig)-binding domains folded into a three-helix bundle. Each of these five domains is able to bind Igs from many different mammalian species. Recombinant SpA is widely used as a component of diagnostic kits for the detection and purification of IgGs from serum or other biological fluids. In this study, purified SpA was adsorbed and covalently linked to Bacillus subtilis spores. Spores are ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…In 2014, Gashtasbi et al [70] immobilized the alpha-amylase enzyme on the spore surface by the covalent method using 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride and N hydroxysulfosuccinimide. In contrast to that study in which just one domain of SpA was displayed, in 2015, Ghaedmohammadi et al [53] displayed both full-length and truncated forms of SpA containing 5 IgG-binding domains on the spore surface. In the latter study, SpA was displayed on the surface of B. subtilis spores by two nongenetically approaches including spontaneous adsorption of SpA onto the spore surface, and covalent linkage of this protein to the spore surface proteins.…”
Section: Surface Display Of Spa On Bacterial and Eukaryotic Cells Formentioning
confidence: 80%
See 3 more Smart Citations
“…In 2014, Gashtasbi et al [70] immobilized the alpha-amylase enzyme on the spore surface by the covalent method using 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride and N hydroxysulfosuccinimide. In contrast to that study in which just one domain of SpA was displayed, in 2015, Ghaedmohammadi et al [53] displayed both full-length and truncated forms of SpA containing 5 IgG-binding domains on the spore surface. In the latter study, SpA was displayed on the surface of B. subtilis spores by two nongenetically approaches including spontaneous adsorption of SpA onto the spore surface, and covalent linkage of this protein to the spore surface proteins.…”
Section: Surface Display Of Spa On Bacterial and Eukaryotic Cells Formentioning
confidence: 80%
“…In contrast to that study in which just one domain of SpA was displayed, in 2015, Ghaedmohammadi et al [53] displayed both full-length and truncated forms of SpA containing 5 IgG-binding domains on the spore surface. They also suggested that the covalent approach is more efficient than adsorption regarding protein attachment to the spore surface [53,71]. The covalent immobilization method using glutaraldehyde as an efficient and low-cost crosslinker had been developed for the first time to display SpA on the spore surface.…”
Section: Surface Display Of Spa On Bacterial and Eukaryotic Cells Formentioning
confidence: 80%
See 2 more Smart Citations
“…SpA is a virulence factor which is located in S. aureus cell wall and is able to bind Fc immunoglobulins (spatially IgG) of the most of mammalians. 34 Therefore, it can be used for the purication of immunoglobulin or Fc conjugated protein from serum or other proteins. Furthermore, the presence of LPxTG motif in its structure makes it suitable to use as a model protein for the sortase-mediated immobilization on different carriers.…”
Section: Introductionmentioning
confidence: 99%